Increasing the Ability of Critical and Creative Thinking of Mathematics Teachers of West Sumatra Senior High Schools through Mathematics Learning Design with Geogebra - Fridgo Tasman (Pelita Eksakta, 2021)
The ability to think critically and the ability to think creatively are two important things in mathematics. These two skills are the focus of learning in the 21st century to prepare students for the challenges of the future. For this reason, it is necessary to provide training for teachers so that they can prepare their students to have these two abilities. For this reason, the team through the community partnership program (PKM) carries out activities to train teachers to be able to design lessons that can improve students' critical and creative thinking skills. The mechanism for implementing PKM activities is carried out using action research steps. In the action phase for the first activity, the teachers will be introduced to critical and creative thinking skills. They are also given examples of learning activities that can improve critical and creative thinking skills by integrating the use of technology such as geogebra software in learning and implementing learning activities into geogebra classrooms. The designed activity will be implemented in schools with the guidance of the PKM team and jointly evaluated in a focus group discussion (FGD) with mathematics MGMP teachers in West Sumatra. The teachers felt an increase in their ability to design lessons, especially by using the geogebra application and being able to implement it into a geogebra classroom.